Effects of 4 weeks of creatine supplementation in junior swimmers on freestyle sprint and swim bench performance - Dawson, B.; Vladich, T.; Blanksby, B. A. (The Journal of Strength and Conditioning Research, 2002)
To determine whether 4 weeks of oral creatine (Cr) supplementation could enhance single freestyle sprint and swim bench performance in experienced competitive junior swimmers, 10 young men and 10 young women (x age = 16.4 +/- 1.8 years) participated in a 27-day supplementation period and pre- and posttesting sessions. In session 1 (presupplementation testing), subjects swam one 50-m freestyle and then (after approximately 5 minutes of active recovery) one 100-m freestyle at maximum speed. Blood lactate was measured before and 1 minute after each swim trial. Forty-eight hours later, height, mass, and the sum of 6 skinfolds were recorded, and a Biokinetic Swim Bench total work output test (2 x 30-second trials, with a 10-minute passive recovery in between) was undertaken. After the pretests were completed, participants were divided into 2 groups (n = 10, Cr; and n = 10, placebo) by means of matched pairs on the basis of gender and 50-m swim times. A Cr loading phase of 20 g x d(-1) for 5 days was then instituted, followed by a maintenance phase of 5 g x d(-1) for 22 days. Postsupplementation testing replicated the presupplementation tests. Four weeks of Cr supplementation did not influence single sprint performance in the pool or body mass and composition. However, 30-second swim bench total work scores for trial 1 and trial 2 increased after Cr (p < 0.05) but not placebo ingestion. Postexercise blood lactate values were not different after supplementation for the 50- and 100-m sprint trials either within or between groups. It was concluded that 4 weeks of Cr supplementation did not significantly improve single sprint performance in competitive junior swimmers, but it did enhance swim bench test performance.